2022
DOI: 10.1038/s41893-022-00970-0
|View full text |Cite
|
Sign up to set email alerts
|

Protected area personnel and ranger numbers are insufficient to deliver global expectations

Abstract: The 2020 global spatial targets for protected areas set by the Convention on Biological Diversity have almost been achieved, but management effectiveness remains deficient. Personnel shortages are widely cited as major contributing factors but have not previously been quantified. Using data from 176 countries and territories, we estimate a current maximum of 555,000 terrestrial protected area personnel worldwide (one per 37 km2), including 286,000 rangers (one per 72 km2), far short of published guidance on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Importantly, our study showed that ranger density has also decreased by 2.4-fold since the mid-1990s, from a median of 92.0 (IQR 59.0-186.0) (James et al, 1999) to 37.9 (IQR 29.7-57.5) rangers per 1000 km 2 PA across selected countries. In contrast, the maximum global PA personnel density is the same as that reported in the 1990s (Appleton et al, 2022;James et al, 1999). We, therefore, conclude that Asia is a relatively underperforming continent in terms of investing in ranger numbers, and many Asian countries were not able to maintain their past ranger density.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Importantly, our study showed that ranger density has also decreased by 2.4-fold since the mid-1990s, from a median of 92.0 (IQR 59.0-186.0) (James et al, 1999) to 37.9 (IQR 29.7-57.5) rangers per 1000 km 2 PA across selected countries. In contrast, the maximum global PA personnel density is the same as that reported in the 1990s (Appleton et al, 2022;James et al, 1999). We, therefore, conclude that Asia is a relatively underperforming continent in terms of investing in ranger numbers, and many Asian countries were not able to maintain their past ranger density.…”
Section: Discussionsupporting
confidence: 76%
“…Although "effective and equitable management" was also emphasized in previous biodiversity targets, known as Aichi Targets (CBD, 2010). However, knowledge of management effectiveness using ranger-based law enforcement largely remains deficient (Appleton et al, 2022;Moore et al, 2018). Therefore, achieving new post-2020 agreements and targets needs to be informed by past performance, not least because this indicates the likelihood of future success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is especially prevalent in the “hollow government” discourse, which criticizes excessive privatization under New Public Management and emphasizes the role of governments in environmental policies and regulations (Steinzor 2007 ; Flournoy 2011 ). In the context of biodiversity conservation, Appleton et al ( 2022 ) argued that the number of PA personnel and rangers is far less than expected to achieve global biodiversity targets, and called for improvements in resourcing. The role of the government is highly expected in transboundary conservation, such as transboundary fisheries, migratory birds, and wildlife trade (Cullis-Suzuki and Pauly 2010 ; Amano et al 2018 ; Borzee et al 2020 ).…”
Section: Governance Of Protected Areasmentioning
confidence: 99%
“…Although most PPPs are suggested to fill the capacity gaps, adequate capacity to coordinate different organizations and stakeholders is required. We consider that the CBD Post-2020 Framework represented by the “30 by 30” target is an excellent opportunity to emphasize the necessary resource provision and initiatives, as argued in Appleton et al ( 2022 ). Further elaboration of the sample size and case studies are required to verify the “governance paradox” phenomenon.…”
Section: Conclusion: Governance Implications For the “30 By 30” Targetmentioning
confidence: 99%